ADVANCES AND CHALLENGES WITH MICRO‐IRRIGATION1. (20th January 2013) - Madramootoo, Chandra A.; Morrison, Jane; Schultz, Bart
ABSTRACT As global concerns surrounding water scarcity and food security escalate, there will be more demand for micro‐irrigation to meet growing food demands. Micro‐irrigation offers many advantages over conventional irrigation methods, including the ability to apply limited amounts of water directly to the crop root zone, incorporation of fertigation, reduced weed and pest infestation, and lower capital and operating costs. In recent decades, there has been considerable growth in the acreage under micro‐irrigation, mainly as a result of lower costs, improvements in filtration and emitter technology, and increased grower confidence in the technology. Research advances and technological improvements have made micro‐irrigation applicable to a more diverse set of applications, cropping systems, and water quality conditions. Cost and availability of water are also major drivers. Research in nano‐ and biofiltration techniques, soil moisture sensors, and precision irrigation shows great promise for the advancement of micro‐irrigation. Nevertheless, several technological challenges remain, especially for non‐row or non‐orchard crops, and in regions where water quality is severely impaired. Innovations in these areas are required, as well as a transfer of the technology to small farmers in water‐scarce regions who traditionally surface irrigate. Copyright © 2013 John Wiley & Sons, Ltd.